Pelaporan Hasil Belajar Pendidikan Agama Islam (PAI) di MI Miftahul Huda Dono Sendang Tulungagung - Reni Marvianasari; Nur Kholis; Luk-Luk Nur Mufidah (STIKes Ibnu Sina Ajibarang, 2024)
Reporting learning outcomes is an important part of the assessment process related to efforts to inform other interested parties about the learning that has been done. The purpose of this study was to determine the reporting of Islamic education learning outcomes at MI Miftahul Huda Dono Sendang Tulungagung. Qualitative research methods. With data collection techniques used interviews, observation and documentation. The data analysis techniques are (1) data condensation, (2) data presentation, and (3) verification and conclusions. The results of his research show that reporting learning outcomes is a process of conveying information about academic progress and student achievement in a curriculum or educational program. The ability of teachers in reporting the evaluation of Islamic Religious Education (PAI) learning outcomes at MI Miftahul Huda Dono Sendang Tulungagung is good. It is proven that PAI teachers have made reports on learning outcomes in the form of report cards, and reports are addressed to students and guardians. Reporting on the evaluation of learning outcomes in PAI subjects at MI Miftahul Huda Dono Sendang Tulungagung, PAI teachers as implementers of learning outcomes evaluation need to compile and prepare well so that the implementation of learning outcomes evaluation in the upcoming school year is really on target in the evaluation, and in accordance with the learning outcomes of the cognitive domain of students.